2006
DOI: 10.1021/jp062895t
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, Structure, and Dynamics in Room Temperature Ionic Liquids:  The Case of 1-Butyl-3-methyl Imidazolium Hexafluorophosphate ([bmim][PF6])

Abstract: A detailed investigation of the phase diagram of 1-butyl-3-methyl imidazolium hexafluorophosphate ([bmim][PF(6)]) is presented on the basis of a wide set of experimental data accessing thermodynamic, structural, and dynamical properties of this important room temperature ionic liquid (RTIL). The combination of quasi adiabatic, continuous calorimetry, wide angle neutron and X-ray diffraction, and quasi elastic neutron scattering allows the exploration of many novel features of this material. Thermodynamic and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
179
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 41 publications
24
179
1
2
Order By: Relevance
“…Two of these phases were previously investigated. 34,35 These experimental results are in contrast with recent results from high pressure DTA and Raman experiments, where only one crystalline phase was discernible up to 2 GPa. 19,20 The existence of different crystalline polymorphs at comparable thermodynamic conditions points to the occurrence of several local conformational minima in the potential energy surface.…”
Section: Introductioncontrasting
confidence: 91%
“…Two of these phases were previously investigated. 34,35 These experimental results are in contrast with recent results from high pressure DTA and Raman experiments, where only one crystalline phase was discernible up to 2 GPa. 19,20 The existence of different crystalline polymorphs at comparable thermodynamic conditions points to the occurrence of several local conformational minima in the potential energy surface.…”
Section: Introductioncontrasting
confidence: 91%
“…Wide-angle X-ray scattering results on the [C 4 mim][I] room temperature ionic liquids show prominent peaks in the residual radial distribution curve [118], indicating certain periodical arrangements of the iodide anions. The existence of different rotamers and local structures has also been found by interpretation of results from optical heterodynedetected Raman-induced Kerr-effect spectroscopy (OHD-RIKES) [139], from neutron scattering and diffraction experiments versus temperature [111][112][113]140], from Coherent anti-Stokes Raman Scattering (CARS) [141] and by theoretical molecular dynamics calculations [43,47,[142][143][144]. The local structures may also lead to other unique properties of ionic liquids; for example, if magnetic anions are aligned in RTILs, novel magnetic liquids will be created [145,146].…”
Section: Conformational Equilibria In Liquids Versus Temperaturementioning
confidence: 87%
“…The structural analysis helps the understanding of solvation of nonpolar, polar, and associating solutes in these media [140,148]. The existence of an extended hydrogen-bonded network structure was suggested by Abdul-Sada et al [65] for 1-alkyl-3-methylimidazolium halides based on results from fast-atom bombardment mass spectroscopy.…”
Section: Local Structures In Ionic Liquidsmentioning
confidence: 99%
“…It was also observed that the degree of charge ordering becomes less pronounced for large anions and asymmetrical cations. [10][11][12][13] Recently, a combination of infrared (IR) spectroscopic techniques was used to characterize the degree of charge organization present in the imidazolium based ionic liquid family. 14 It was found that longer alkyl side chains attached onto the imidazolium ions increase the short-range repulsive interactions among the ions and disrupt the charge organization, in agreement with previous studies.…”
Section: Introductionmentioning
confidence: 99%